Analisis Penerapan Collaborative Governance dalam Pengelolaan Pariwisata Bencana Lava Tour - Diani, Rintan Mirza; Simbolon, Yoanes Kevin Gratianus (Forum Ilmu Sosial, 2017)
Public affairs that get more complicated these days, forces the government to implement collaborative governance with the involved parties. One of the actions of implementing the collaborative governance is seen through management of Lava Tour in Merapi. The increasing number of society's interest in visiting the tourism site, inundates the government. Therefore, the government has to cooperate with private, and also with the citizen. This paper explains further about the form of collaborations that are conducted by the government, private, and the citizen. Based on the analysis, the form of collaboration that is conducted is Partnership that suits Bryson's (2014) classification.